Asymmetric construction of six vicinal stereogenic centers on hexahydroxanthones via organocatalytic one-pot reactions. Issue 55 (16th June 2021) - Zhang, Min; He, Xue-Wen; Xiong, Ya; Zuo, Xiong; Zhou, Wei; Liu, Xiong-Li
Abstract : Inspired by the chemistry and biology of hexahydroxanthones, herein we report an asymmetric organocatalytic strategy enabling the first construction of six vicinal stereogenic centers on non-spirocyclic hexahydroxanthone frameworks. Abstract : Inspired by the chemistry and biology of hexahydroxanthones, herein we report an organocatalytic Michael–Michael–Aldol-decarboxylation reaction that provides efficient access to biologically interesting fully substituted hexahydroxanthones bearing six contiguous stereogenic centers from readily accessible materials in acceptable yields (up to 63%) and excellent stereoselectivities (up to 10 : 1 dr and >99% ee). In other words, the reaction efficiently produces three chemical bonds and up to six vicinal stereogenic centers in a one-pot operation. In particular, to our knowledge, this is an asymmetric organocatalytic strategy enabling the first construction of six vicinal stereogenic centers on non-spirocyclic hexahydroxanthone frameworks.